Cystic Fibrosis with Paediatric Femoral Neck Stress Fracture: A Case Report and the Review of Literature - Yavuz Şahbat; Ahmet Hamdi Akgülle (Galenos Yayinevi, 2021)
Cystic fibrosis is a common genetic disease of the white population with autosomal recessive inheritance. It may present with sinopulmonary, gastrointestinal, genitourinary, bone and joint findings. Osteoporosis, osteopenia, and fractures are musculoskeletal problems related to the disease. Although vertebral fractures are common, non-vertebral fractures have been reported rarely. In this case report, we present the case of a 9-year-old girl with osteopenia-induced femoral neck stress fracture caused by cystic fibrosis. During hospitalization for sinopulmonary infection, the patient presented to our clinic with left thigh pain without trauma. The left hip joint was examined and found to be clear. Anterior posterior X-ray examination of the patient, who had difficulty in stepping, revealed no displaced fracture. The patient was later diagnosed with type 2 Fullerton & Snowdy fracture, and surgical fixation was ruled out. The patient was successfully treated with non-steroidal anti-inflammatory drugs and immobilization.